2014
DOI: 10.1038/pcan.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and health factors associated with progressing and remitting trajectories of untreated lower urinary tract symptoms among elderly men

Abstract: BackgroundKnowledge of factors associated with the course of lower urinary tract symptoms (LUTS) before treatment is needed to inform preventive interventions. In a prospective study of elderly men untreated for LUTS, we identified factors associated with symptom progression and remission.MethodsIn community dwelling U.S. men age ≥ 65 years, the American Urological Association Symptom Index (AUA-SI) was repeated four times, once at baseline (2000–2002) and then every two years thereafter. Analyses included 174… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 48 publications
(73 reference statements)
1
33
0
5
Order By: Relevance
“…[16] In addition, being overweight was associated with a significantly higher risk for symptomatic progression based on the IPSS in a prospective study of 1740 elderly men ≥65 years old. [17] A separate study found that a greater abdominal fat mass predicted the progression of LUTS symptoms in a population based cohort of 780 men. [11] Finally, obesity also predicts a poorer response to standard therapies for LUTS.…”
Section: Methodsmentioning
confidence: 99%
“…[16] In addition, being overweight was associated with a significantly higher risk for symptomatic progression based on the IPSS in a prospective study of 1740 elderly men ≥65 years old. [17] A separate study found that a greater abdominal fat mass predicted the progression of LUTS symptoms in a population based cohort of 780 men. [11] Finally, obesity also predicts a poorer response to standard therapies for LUTS.…”
Section: Methodsmentioning
confidence: 99%
“…During follow-up, the cohort for trajectory analysis was further restricted to 1740 men who remained free from diagnosed prostate cancer, reported no surgery or medication use for LUTS, and completed all four AUA-SI assessments. A figure demonstrating how the analytic cohort was ascertained for the trajectory analysis has been previously published [26]. The same study demonstrated no significant differences in LUTS trajectory among men with a history of stroke and those who used CNS medications [26], so we did not exclude them from the present analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A figure demonstrating how the analytic cohort was ascertained for the trajectory analysis has been previously published [26]. The same study demonstrated no significant differences in LUTS trajectory among men with a history of stroke and those who used CNS medications [26], so we did not exclude them from the present analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations